Designing a Relational Database Model Using Normalization Techniques in the Independent Practice Midwife Service Data Archiving Application - Dahlia Widhyaestoeti; Rizki Kristia Akmal; Jejen Jaenudin; Fitria Rachmawati (Universitas Ibn Khaldun Bogor, 2023)
Health services at Independent Practice Midwife (BPM) Wita Utami Awaliyah, S.ST, for patients include pregnancy checks, family planning (KB), and general check-ups. Archiving service data still uses folio book media and is stored in Bantex boxes. The process of recording and searching data services for Practical Midwives requires a web-based application. The digital form of service is designed by collecting Pregnancy Check Archive Data, Family Planning Archive Data and General Check Archive Data, then carrying out a normalization technique process to convert the data into a good relational data model. The system development method is created using the Waterfall model, and system design uses UML diagrams. The application was built using PHP, Javascript, MySQL and the Laravel framework. The results of feature testing using the Blackbox method show the success of each feature of the Web-Based Independent Practice Midwife Service Data Archiving Application from the test class test results with the expected output.